2021
DOI: 10.5114/pjr.2021.111437
|View full text |Cite
|
Sign up to set email alerts
|

Application of shear wave elastography and median nerve cross-section area in the diagnosis and staging of carpal tunnel syndrome: a case-control study

Abstract: Purpose Imaging is gaining a more prominent role in the diagnosis of carpal tunnel syndrome (CTS), especially ultrasonography. Shear wave elastography (SWE) is a novel qualitative method to study mechanical changes in tissue. In this study, we aim to assess the role of SWE in diagnosing and staining of the disease. Material and methods A total of 124 wrists were included in the study. Seventy wrists had CTS, and 54 were included as the control group. All of the wrists w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Therefore, the influence of training confirms that cycling exerts compression causing oedema in both nerves as their CSA increases. However, the rise in stiffness that depends of fibrosis [ 23 ] is pronounced more than CSA that depends on oedema. This phenomenon deserves clarification.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the influence of training confirms that cycling exerts compression causing oedema in both nerves as their CSA increases. However, the rise in stiffness that depends of fibrosis [ 23 ] is pronounced more than CSA that depends on oedema. This phenomenon deserves clarification.…”
Section: Discussionmentioning
confidence: 99%
“…SWE allows quantitative measurement of tissue stiffness or elasticity by tracking the propagation of shear waves generated by the US transducer. [8][9][10] Studies have reported increased MN stiffness or elasticity correlating with CTS severity, as the nerve undergoes biomechanical changes due to compression. [10][11][12][13] While both US and SWE have shown promise individually in CTS diagnosis, there is a paucity of research investigating their combined diagnostic performance in comprehensively evaluating CTS.…”
Section: Introductionmentioning
confidence: 99%
“…With different targeting CTS cases and using either static strain elastography (tissue compression produces strain)[ 5 ] or share wave elastography (focused acoustic radiation force from a linear ultrasound array),[ 6 ] MN stiffness was reported, and its elastoscan determined the early pathophysiological changes that are caused by CTS. [ 7 - 10 ]…”
Section: Introductionmentioning
confidence: 99%
“…With different targeting CTS cases and using either static strain elastography (tissue compression produces strain) 5 or share wave elastography (focused acoustic radiation force from a linear ultrasound array), 6 MN stiffness was reported, and its elastoscan determined the early pathophysiological changes that are caused by CTS. [7][8][9][10] This study is an extension of the study by Lasheen et al, 11 which aimed to compare CTS patients and healthy volunteers regarding the ultrasound and sonoelastography (SE) of the MN at the wrist and the later correlation to nerve conduction study (NCS) results and included increased stiffness of MN affected by CTS with positive correlations with NCSs. In this paper, we focused on the symptomatic and the functional evaluation in correlation to MN elasticity, its ultrasound parameters, and the electrodiagnostic grading of primary CTS patients.…”
mentioning
confidence: 99%